Wind Turbine Gearbox Failure Detection Through Cumulative Sum of Multivariate Time Series Data - Latiffianti, Effi; Sheng, Shawn; Ding, Yu (Frontiers in Energy Research, 2022)
The wind energy industry is continuously improving their operational and maintenance practice for reducing levelized costs of energy. Anticipating failures in wind turbines enables early warnings and timely intervention, so that the costly corrective maintenance can be prevented to the largest extent possible. It also avoids production loss owing to prolonged unavailability. One critical element allowing early warning is the ability to accumulate small-magnitude symptoms resulting from the gradual degradation of wind turbine systems. Inspired by the cumulative sum control chart method, this study reports the development of a wind turbine failure detection method with such early warning capability. Specifically, the following key questions are addressed: what fault signals to accumulate, how long to accumulate, what offset to use, and how to set the alarm-triggering control limit. We apply the proposed approach to two years worth of operational data recorded from five wind turbines. We focus our analysis on gearbox failures detection, in which the proposed approach demonstrates its ability to anticipate failure events with a good lead time.